Konsep dasar membaca di SDIT Insan Permata - Nadhifah, Nisaun (Maliki Interdisciplinary Journal, 2023)
Learning is a system consisting of various components that are interconnected with one another. These components include objectives or competencies, materials, methods, and evaluation. Learning to read is important at the elementary school stage. Reading learning is divided into two, namely beginner reading learning and advanced reading. Beginner reading places more emphasis on the sound symbols of language while further reading emphasizes the meaning of the text being read. A person is said to be skilled at reading if he can convey the meaning and form of written language (in the form of words, sentences, paragraphs, composition of writing) that he reads, therefore reading is a language skill besides symbols. In addition to the sound of language and its meaning, reading can also add to the learner’s vocabulary.